Title: priority areas for genetic conservation of Eremanthus erythropappus (DC.) MacLeish in Brazil - Padua, Joelma Aparecida Rabelo de; Rocha, Lucas Fernandes [UNESP]; Brandao, Murilo Malveira; Almeida Vieira, Fabio de; Carvalho, Dulcineia de (Springer, 2021)
Eremanthus erythropappus (DC.) MacLeish, commonly known as candeia, is a threatened tree species that occurs in Seasonal Semideciduous Forests in Brazil. The tree is valued for the durability of its wood and essential oil production, from which the active agent (alpha-bisabolol) is used in pharmaceutical and cosmetic industries. Due to its high economic value, E. erythropappus has been exploited for several decades. Natural populations have been reduced, with the subsequent ecological and genetic negative impacts. We aimed to use a landscape genetics approach to identify if natural features influence the genetic diversity of E. erythropappus. In order to assess the genetic variability and provide information for the conservation of the species, genetics analyses were carried out for 200 individuals from ten natural populations of E. erythropappus. Nine ISSR primers produced 72 bands, of which 57 (79%) were polymorphic. Genetic diversity (H-E) was 0.30 and gene flow was 1.4 migrants per population. The Bayesian clustering model indicated the occurrence of four genetically distinct populations (K = 4). Results of AMOVA showed high genetic differentiation between populations (30.8 %) and there was positive correlation between genetic and geographic distances (r = 0.632, P = 0.001). Based on a Mantel correlation and the genetic discontinuity among populations, we recommend the implementation of four operational units to support the conservation of this species.
Keywords: ISSR; Genetic diversity; Forest management; Candeia; Brazilian savannah; Atlantic forest